KINERJA KEUANGAN BADAN USAHA MILIK DESA - Fitri, Nurul; Septiani, Indri; Nurmiati, Nurmiati (Patria Artha Journal of Accounting dan Financial Reporting, 2025)
This study aims to determine and analyze the financial performance of Village-Owned Enterprises (BUMDes) in Kaburu Village, Bontomanai District, Selayar Islands Regency for 2020-2022, based on aspects of financial ratios consisting of Liquidity Ratio, Profitability Ratio, Solvency Ratio and Activity Ratio. This research uses a descriptive method with a quantitative approach with analysis techniques using financial ratio calculation analysis. In this study the data used is the financial statements of the Village-Owned Enterprises (BUMDes) Bukit Harapan Kaburu Village for three periods from 2020 to 2022. The results of the study indicate that in general the financial performance of the Village-Owned Enterprise (BUMDes) "Bukit Harapan" Kaburu Village, Bontomanai District, Selayar Islands Regency is good in terms of liquidity ratio, profitability, solvency and activity. This shows that BUMDes Bukit Harapan must maintain these four ratio and better improve them.